Clinical Value of Ureteral Catheterization before Trans-abdominal Radical Hysterectomy and Pelvic Lymphadenectomy - Zhang, Yong; Yin, Xiao-Ying; Liu, Jin-Xia (Nepalese Journal of Cancer, 2022)
Introduction: Being in the close vicinity, chances of ureteral injury is high while doing radical operation for cervical cancer. Although the incidence is low, if it is not found during the operation, it can lead to serious complications such as urinary fistula. Timely detection and repair of ureteral injury can reduce the occurrence of serious complications.The placement of ureteral catheter before radical hysterectomy can be a good method to identify the ureter during operation to prevent injury.The objective of the study was to explore the advantages and disadvantages of the placement of ureteral catheter in radical operation of cervical cancer. Methods: 103 patients who were diagnosed as cervical cancer and underwent operation in the department of Obstetrics and Gynecology, Jinling Hospital from January 2019 to April 2020 were analyzed in this study. The clinical stage ranges from IA to IIA. Among them, 23 cases were placed with double J stent before operation (observation group), 80 cases were operated without stent (control group). The intra-operative condition, operation and postoperative complications were analyzed retrospectively. Results: There was a significant difference in the operation time and intra-operative blood loss between the two groups (P< 0.05), and there was no significant difference in blood transfusion between the two groups (P> 0.05). There was no significant difference in the incidence of urinary tract infection and urinary retention between the two groups (P> 0.05). The incidence of postoperative hematuria (including microscopic hematuria) was significant in two groups（P< 0.05). Ureteric injury occurred in the 9 patients in the control group (11.25%). Conclusion: Ureteral catheter inserted before radical operation of cervical cancer can help to identify the ureter easily, decrease urinary tract injury, shorten operation time and reduce intra-operative blood loss, and will not increase urinary retention and urinary tract infection. It is safe and effective method especially for young gynecologists.